Catalyst-free sulfa-Michael addition of pyrimidine-2-thiol to nitroolefins. (2nd November 2017) - Li, Zheng; Song, Geyang; He, Jiaojiao; Du, Yan; Yang, Jingya
ABSTRACT: Catalyst-free sulfa-Michael addition of pyrimidine-2-thiol to nitroolefins is described. A series of 2-((2-nitro-1-arylethyl)thio)pyrimidines were efficiently synthesized. The protocol has advantages of wide range of substituents tolerance, no catalyst, additives and bases, mild condition, and high yield. The method can also extend to gram scale. GRAPHICAL ABSTRACT: